Implementation of Smart Record System Based on Face Detection for Teacher Attendance Recording and Reporting Based on IoT - Hermawan, Indra; Yulianti, Susana Dwi; Murad, Fachroni Arbi; Setianto, Bayu Dwi; Fadil Azhar, Raden Muhammad; Sutama, Muhammad Ilham (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Teachers and staff at Sekolah Alam Indonesia (SAI) Cibinong have been using a manual attendance system, which has caused delays in attendance recapitulation and inefficiencies in reporting and monitoring. To address this problem, the Participatory Action Research (PAR) method was adopted, emphasizing active involvement from the school community in every stage of the program. The PAR method was chosen because it fosters a collaborative approach, ensuring that the solution is tailored to the specific needs and context of the school. The Smart Record System, an automated Internet of Things system that uses facial detection technology for precise attendance recording and reporting, was introduced by the community service program to address this problem. To increase participants' understanding of data security, this program offered a seminar on Personal Data Protection in social media and system implementation. To guarantee efficient use of the technology, the methodology included system installation, integration with IoT components, and training sessions. After providing participants with practical system operation experience, system assessments and feedback gathering were conducted to gauge the implementation's efficacy. The outcomes demonstrated how the smart attendance system, which offered real-time attendance data and prompt reporting, greatly simplified the attendance management procedure. Based on the questionnaire responses, the system achieved an average user satisfaction score of 3.86 out of 5, reflecting a 77.2% positive agreement among users. Furthermore, the reliability of the questionnaire, measured by Cronbach’s Alpha, was 0.85, indicating a high level of consistency in the responses. These quantitative findings confirm that the system significantly improved the efficiency of attendance management while being well-received by teachers and staff.